PENDIDIKAN KEMARITIMAN UNTUK ANAK USIA DINI - SARILAH SARILAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The purpose of this maritime education is to realize the personality of students both attitudes, knowledge, and skills related to maritime or marine from an early age in order to strengthen the competence of students, and can equip PAUD / Kindergarten teachers in recognizing the abilities of children, especially those who live in coastal areas. The target of this training is given to PAUD/TK teachers from various PAUD/TK institutions in Jonggat sub-district as many as 30 teachers, maritime education content that can be introduced to children includes maritime history, maritime potential, values ??of love for the homeland and positive character. from maritime. so it requires teachers who are able to master the class, students, learning methods and skilled creativity. The hope of this activity is that with the knowledge possessed about maritime education, it is hoped that PAUD / Kindergarten teachers are able to carry out maximum learning adapted to the growth and development of children and their abilities to achieve optimal development. ABSTRAK Tujuan pendidikan kemaritiman ini untuk mewujudkan kepribadian peserta didik baik sikap, pengetahuan, maupun keterampilan terkait kemaritiman atau kelautan sejak usia dini dalam rangka penguatan kompetensi peserta didik, serta dapat membekali guru PAUD/TK dalam mengenal kemampuan anak. Adapun sasaran pelatihan ini diberikan pada guru-guru PAUD/TK dari berbagai lembaga PAUD/TK di kecamatan jonggat sebanyak 30 guru, muatan pendidikan kemaritiman yang dapat diperkenalkan pada anak antara lain sejarah maritim, potensi kemaritiman, nilai-nilai cinta tanah air dan karakter positif dari kemaritiman. sehingga memerlukan guru yang mampu untuk menguasai kelas, siswa, metode pembelajaran serta kreativitas yang terampil. Harapan dari kegiatan ini yaitu dengan pengetahuan yang dimiliki tentang pendidikan kemaritiaman diharapkan guru PAUD/TK mampu melakukan pembelajaran yang maksimal disesuaikan dengan tumbuh kembang anak dan kemampuanya untuk mencapai perkembangan yang optimal.